Innovative Teaching: A Proposed Immersive Reader Training Program for Special Needs Teachers - Osman, Fadzillah Mohamed (Journal of ICSAR, 2024)
This concept paper presents a training program aimed at empowering teachers of special needs students at Tasik Puteri 2 Primary School to effectively utilize immersive reader technology in their classrooms. Immersive reader serves as an assistive technology tool that enhances reading and writing skills among students with special needs by offering customizable visual and auditory aids. The training program is developed following a needs assessment and encompasses workshops, hands-on practice, and online resources, enabling teachers to comprehend the technology's functionalities and tailor it to suit their special needs students. Continuous support and monitoring ensure successful integration of the technology, while collaborative efforts among educators create a nurturing learning environment. By implementing immersive reader technology, the paper anticipates providing special needs students with enhanced engagement opportunities, potentially reducing the academic achievement gap between them and their peers.